Polymeric Composite Materials Based on Polyethylene and Modifying Additives - Rosilov Mansur Sirgiyevich; Nomozova Sadoqat iskandar qizi; Tog’ayev Eldor Maxmanazarovich (International Journal on Orange Technologies, 2022)
The article presents the results of research on the development of polymer composite materials with improved strength and antifriction properties based on high-density polyethylene (HDPE), as well as low-density polyethylene (LDPE) and modifying additives - Azerbaijani clays and SAE5W30 motor oil. It has been established that the introduction of 5–25% nanosized clays and 1–3% of the above oil into the composition allows thermoplastic materials with sufficiently high antifriction and other properties.